2006
DOI: 10.1007/s00464-005-0713-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoloop-assisted polypectomy for large pedunculated colorectal polyps

Abstract: Colonoscopic polypectomy with an endoloop may be safer than conventional polypectomy. The reasons for technical failure of this technique include a narrow left colon lumen, a thin stalk (< or = 4 mm), and close cutting in relation to the site of encirclement by the loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 21 publications
0
38
2
Order By: Relevance
“…On the basis of our results, it is possible to consider endoloop-assited polypectomy in large pedunculated colorectal polyps a safe procedure, irrespective of the diameter of the stalk, contrasting with the data from Katsinelos et al [1] and Matsushita et al [5], but in accordance with Rey and Marek [6] and Iishy et al [7]. Probably, our data are the result of a methodological approach to this technique different from Katsinelos et al [1]: in fact we approach all polypertomies with the same fear of precipitating hemorrhage irrespective of the application of the endoloop.…”
contrasting
confidence: 84%
See 1 more Smart Citation
“…On the basis of our results, it is possible to consider endoloop-assited polypectomy in large pedunculated colorectal polyps a safe procedure, irrespective of the diameter of the stalk, contrasting with the data from Katsinelos et al [1] and Matsushita et al [5], but in accordance with Rey and Marek [6] and Iishy et al [7]. Probably, our data are the result of a methodological approach to this technique different from Katsinelos et al [1]: in fact we approach all polypertomies with the same fear of precipitating hemorrhage irrespective of the application of the endoloop.…”
contrasting
confidence: 84%
“…Thus, by rereading in this manner the results reported by Katsinelos et al [1], endoloop appears ineffective in comparison with Matsushita et al [5] and in contrast to the results reported by Rey and Marek [6] and by Iishy et al [7] in the only published randomized trial (no bleeding in the 47 patients in the endoloop arm and five cases of bleeding in the 42 patients of the control arm), the largest series until now available.…”
mentioning
confidence: 43%
“…These conclusions were observed in subsequent retrospective studies. 14 However, the use of the endoloop could pose greater technical difficulties due to transection by the loop of a thin stalk before the polypectomy or insufficient tightening of the loop. 15 Moreover, we must remember that there are difficulties in looping big polyps with the endoloop and in the ultimate subsequent snaring of the polyp.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-tied ligature systems, also known as endoscopic slipknots or "endoloops", are composed of a slipknot and a laparoscopic tool used to guide and tighten the knot, which is known as knot pusher (KATSINELOS et al, 2006). Hemostasis is achieved by pushing and tightening the knot around the ovarian pedicle.…”
Section: Clinic and Surgerymentioning
confidence: 99%